One Step Forward, One Step Back? The Crime of Aggression under the Rome Statute The Crime of Aggression under the Rome Statute - Béres, Nóra (The ICC at 25: Lessons Learnt, 2025)
By activating the Kampala Amendments to the Rome Statute, for the first time since the Nuremberg and Tokyo trials after the Second World War, the International Criminal Court (ICC) has jurisdiction over crime of aggression. This is one giant leap for mankind; nevertheless, the international community will likely have to wait a long time to witness a criminal procedure before the ICC initiated for the crime of aggression. This is because it is not the complete disappearance of the breaching of the rules of jus contra bellum, but the complex and almost inapplicable set of rules on the crime of aggression. To see these obstacles clearly, this article seeks to provide a concise analysis of the definition of the crime of aggression (“substantial aspects”) and the exercise of jurisdiction over the crime of aggression (“procedural aspects”) in accordance with the respective provisions of the Rome Statute. Keywords: international criminal law, Rome Statute, International Criminal Court, Kampala Amendments, the crime of aggression